Peran Pesantren dalam Melakukan Perubahan Sosial Lingkungan Sekitarnya - Fahiani, Aulia Nurul; Amriati, Ulil; Rosidah, Fahmi; Fitriani, Laili; Taufiqurrahman, Taufiqurrahman (Lembaga Yasin AlSys, 2026)
Although the role of pesantren has been widely discussed in previous studies, research that specifically examines the role of pesantren in driving social change, particularly in Indonesia, remains limited. This study aims to analyze the role of pesantren in social change across historical periods, describe the core values of pesantren education, and explain the role of pesantren in social change in Indonesia. The study employs a qualitative approach with a library research design and descriptive analysis of various relevant literature sources. The findings show that pesantren actively promote social change in their surrounding communities through the internalization of foundational pesantren educational values that are not found in general schooling, particularly within the Indonesian pesantren context. These findings enrich analysis and broaden understanding of the role of pesantren in processes of social change, while also opening avenues for further exploration and critical examination of the role of pesantren and social change in the contemporary modern era.